FINANCIAL BEHAVIORAL BIASES (PRESENT BIAS AND OVERCONFIDENCE) ON CONSUMER DEBT DECISION MAKING AMONG MANUFACTURING WORKERS IN BATAM - Etty Sri Wahyuni; Henry Aspan; Faris Ramadhan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study investigates the influence of present bias and overconfidence on consumer debt decision-making among manufacturing workers in Batam, Indonesia, incorporating financial literacy as a moderating variable. Batam, a strategic free trade zone and major industrial hub, faces a growing phenomenon of consumer over-indebtedness fueled by the rapid expansion of digital lending platforms and online loans among its workforce. A quantitative cross-sectional survey design was employed, with a sample of 215 manufacturing workers drawn from Batam’s major industrial estates through purposive sampling. Data were collected via validated Likert-scale questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The findings reveal that: (1) present bias exerts the strongest positive and significant effect on consumer debt decisions (β = 0.387; p < 0.001); (2) overconfidence positively and significantly affects consumer debt decisions (β = 0.294; p < 0.001); (3) financial literacy significantly weakens the relationship between present bias and consumer debt decisions (β = –0.168; p < 0.01); however, (4) financial literacy does not significantly moderate the relationship between overconfidence and consumer debt decisions (β = –0.074; p > 0.05). These findings reveal an asymmetric moderation effect, indicating that conventional financial education is effective in mitigating present bias but insufficient in reducing overconfidence, which requires fundamentally different intervention approaches targeting metacognition rather than knowledge acquisition. The study contributes to behavioral finance literature by extending the application of hyperbolic discounting and overconfidence theories to consumer debt contexts in developing-country industrial zones and offers practical implications for financial regulators and corporate financial wellness programs.